2011
DOI: 10.1371/journal.pone.0026106
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Expression Does Not Correlate with Serum Alkaline Phosphatase Concentration in Canine Osteosarcoma Patients

Abstract: Osteosarcoma is an aggressive malignancy of the bone and an increase in serum alkaline phosphatase concentration has clinical prognostic value in both humans and canines. Increased serum alkaline phosphatase concentration at the time of diagnosis has been associated with poorer outcomes for osteosarcoma patients. The biology underlying this negative prognostic factor is poorly understood. Given that activation of the Wnt signaling pathway has been associated with alkaline phosphatase expression in osteoblasts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In accordance with that, no mutation has been recently identified in canine β-catenin exon 3, similarly to human OSA [19], even if a limited number of cases were examinated, and a mainly cytoplasmic, but rare nuclear localization of the protein was detected [51]. Furthermore, no differences in nuclear β-catenin immunohistochemical expression were observed in samples obtained from two populations of canine OSA patients with normal or high level of serum alkaline phosphatase concentration [52], known to have negative prognostic value in canine osteosarcoma patients [53]. These results seem to be in agreement with recent investigations in human OSA [26], where no β-catenin nuclear expression was observed in 90% of human high grade OSA biopsies examinated and inhibition of the Wnt/β-catenin pathway has been demonstrated to be important in osteoblast neoplastic transformation [26].…”
Section: Discussionmentioning
confidence: 65%
“…In accordance with that, no mutation has been recently identified in canine β-catenin exon 3, similarly to human OSA [19], even if a limited number of cases were examinated, and a mainly cytoplasmic, but rare nuclear localization of the protein was detected [51]. Furthermore, no differences in nuclear β-catenin immunohistochemical expression were observed in samples obtained from two populations of canine OSA patients with normal or high level of serum alkaline phosphatase concentration [52], known to have negative prognostic value in canine osteosarcoma patients [53]. These results seem to be in agreement with recent investigations in human OSA [26], where no β-catenin nuclear expression was observed in 90% of human high grade OSA biopsies examinated and inhibition of the Wnt/β-catenin pathway has been demonstrated to be important in osteoblast neoplastic transformation [26].…”
Section: Discussionmentioning
confidence: 65%
“…Often, the presence of cytoplasmic and/or nuclear localization of β ‐catenin is used as surrogate for pathway activation. While both humans and canines exhibit frequent cytoplasmic β ‐catenin staining, there is minimal nuclear β ‐catenin staining, with 10% (5/52) of human OS samples and 2% (1/56) to 10% (3/30) of canine OS samples displaying positive nuclear β ‐catenin . Contrary to these low numbers, Bongiovanni et al observed 47% (8/17) of canine OS samples to display nuclear staining; however, in nuclear‐positive samples, less than 10% of nuclei/cells within the sample were positive, indicating that these positive nuclei were very weakly positive.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options and survival rates for both human and canine OS have essentially stagnated the last 15–20 years, prompting the investigation of various molecules and signalling pathways that could be targeted for therapy in hopes of improving outcomes . Wnt signalling is a pathway of interest for its role in osteoblast differentiation, its dysregulation in numerous cancer types, and the frequency of cytoplasmic accumulation in canine and human OS . While in epithelial‐based cancers – such as hepatocellular, colorectal and mammary carcinomas – β ‐catenin activation is considered a pro‐oncogenic alteration, the role of β ‐catenin in mesenchymal‐based tumours such as melanoma and OS is less well‐defined .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed that positive cytoplasmic β -catenin expression was associated with the development of metastasis both in vivo and in vitro [9, 5254]. Although the deregulation of β -catenin is thought to play an important role in oncogenesis of osteosarcomas, the role of Wnt signaling in osteosarcomas remains controversial [18, 22, 53, 55, 56]. Recently, a study has indicated that β -catenin may interact with other proteins, such as NF-kappa B, during oncogenesis [57].…”
Section: Discussionmentioning
confidence: 99%